Fourier–Hermite decomposition of the collisional Vlasov–Maxwell system: implications for the velocity-space cascade. (21st March 2019) - Pezzi, O; Valentini, F; Servidio, S; Camporeale, E; Veltri, P
Abstract: Turbulence at kinetic scales is an unresolved and ubiquitous phenomenon that characterizes both space and laboratory plasmas. Recently, new theories, in situ spacecraft observations and numerical simulations suggest a novel scenario for turbulence, characterized by a so-called phase-space cascade—the formation of fine structures, both in physical and velocity-space. This new concept is here extended by directly taking into account the role of inter-particle collisions, modeled through the nonlinear Landau operator or the simplified Dougherty operator. The characteristic times, associated with inter-particle correlations, are derived in the above cases. The implications of introducing collisions on the phase-space cascade are finally discussed.